Biodiversity and Resilience of Ecosystem Functions. (November 2015) - Oliver, Tom H.; Heard, Matthew S.; Isaac, Nick J.B.; Roy, David B.; Procter, Deborah; Eigenbrod, Felix; Freckleton, Rob; Hector, Andy; Orme, C. David L.; Petchey, Owen L.; Proença, Vânia; Raffaelli, David; et al.
Abstract : Accelerating rates of environmental change and the continued loss of global biodiversity threaten functions and services delivered by ecosystems. Much ecosystem monitoring and management is focused on the provision of ecosystem functions and services under current environmental conditions, yet this could lead to inappropriate management guidance and undervaluation of the importance of biodiversity. The maintenance of ecosystem functions and services under substantial predicted future environmental change (i.e., their 'resilience') is crucial. Here we identify a range of mechanisms underpinning the resilience of ecosystem functions across three ecological scales. Although potentially less important in the short term, biodiversity, encompassing variation from within species to across landscapes, may be crucial for the longer-term resilience of ecosystem functions and the services that they underpin.